EFETIVIDADE DAS DECLARAÇÕES DE MISSÃO INSTITUCIONAL: ANÁLISE DAS DECLARAÇÕES DAS INSTITUIÇÕES FEDERAIS DE ENSINO SUPERIOR (IFES) - Claudio Luiz de Freitas (Universidade Federal de Santa Catarina, 2019)
The institutional mission of an organization, if well elaborated, constitutes an important tool to support strategic management. Thus, this study aims to analyze the status quo of the institutional mission of Federal Institutions of Higher Education in Brazil, from the elements proposed by Pearce (1982) and Pearce and David (1987). For this, the methodology adopted is divided into three parts: literature review, data collection and analysis results. The study has a descriptive feature with a qualitative approach to the problem and use of secondary source research. The results reveal that, according to studies of Pearce (1982) and Pearce and David (1987), none of the Brazilian Federal Institutions of Higher Education has comprehensive effectiveness of the institutional mission. The elements that were identified most frequently were "reference to the product or service" and "commitment to sustainable development (economic / social / environmental)", while the elements that refer to "organization philosophy and values" and "organization image" were little remembered in the mission statements. The conclusion from the comparative analysis of the status quo of Federal Institutions of Higher Education mission, by region of the country, is that the south and southeast universities focus institutional missions that are more effective and that elements such as reference to workforce and other stakeholders are not addressed in none of the institutions.